Periodic Solutions for a Prescribed Mean Curvature Equation with Multiple Delays. (26th May 2014) - Lu, Shiping; Lu, Ming
Abstract : We study the existence of periodic solutions for the one-dimensional prescribed mean curvature delay equation ( d / d t ) ( x ' ( t ) / 1 + x ' t 2 )   + ∑ i = 1 n a i t g x t - τ i t = p t . By using Mawhin's continuation theorem, a new result is obtained. Furthermore, the nonexistence of periodic solution for the equation is investigated as well.